Removal of Some Heavy Metal Cations from Aqueous Solution by Adsorption onto Natural Kaolin - H. Ceylan; T. Şahan; R. Gürkan; Ş. Kubilay (Adsorption Science & Technology)
The adsorption removal of some heavy metal cations such as Cu(II), Zn(II) and Co(II) from aqueous solution onto kaolin has been studied using the batch method with initial metal ion concentrations within the range 15–70 mg/l. The percentage adsorption and equilibrium concentrations were determined by means of atomic absorption flame photometry as a function of adsorbate concentration, pH and temperature. Ion-exchange studies showed that over the complete concentration range studied the adsorption ratios for metal cations adsorbed onto kaolin correlated with the linear forms of the Langmuir, Freundlich and Dubinin—Kaganer—Radushkevich (DKR) adsorption isotherms. The cationexchange capacity of kaolin towards each metal ion studied was evaluated. It was found that the adsorption phenomena depended on the charge density and diameter of the hydrated ion. The equilibrium studies demonstrated that the selectivity of the ions followed the sequence Zn(II) > Cu(II) > Co(II) at pH 7.0. Calculation of thermodynamic parameters such as the standard enthalpy (ΔH 0 ), Gibbs free energy (ΔG 0 ) and entropy (ΔS 0 ) showed that the adsorption of the heavy metal ions studied onto kaolin was an endothermic process which was favoured at higher temperatures. These results show that natural kaolin has a considerable potential for the removal of heavy metal cationic species from aqueous solution and wastewater.